The propaganda front : postcards from the era of World Wars : the Leonard A. Lauder Postcard Archive - Jozefacka, Anna; Klich, Lynda; Kreinik, Juliana D.; Weiss, Benjamin (MFA Publications, Museum of Fine Arts, Boston, 2017)
"A socialist worker raises the red flag. Adoring crowds greet Hitler and Mussolini. Uncle Sam orders Americans to enlist. In the first half of the twentieth century, these images and many more circulated by the millions on postcards that were designed to change minds and inspire actions. Whether produced by government propaganda bureaus, opportunistic publishers, aid organizations or resistance movements, postcards conveyed their messages with striking graphics, pithy slogans and biting caricatures -- and in a uniquely personal form. The more than 350 cards reproduced in full color in this book advocate for political causes and celebrate war efforts on all sides of the major conflicts of their time. The accompanying text shows how a ubiquitous form of communication served increasingly sophisticated campaigns in an age of propaganda, and highlights the postcards collected here as both priceless historical documents and masterworks of graphic design." -- Book jacket